Social and political profile of Argentina, Chile and Peru. - Chan, Puay Ser. (2008)
Democracy in Latin America has been reborn, coming out from a period of military rules, political instability, corruption and injustice. Economies are improving and wealth is growing. Disappointingly, not much of this wealth has trickled down, as one-third of all Latin Americans are still living in poverty. However, some of these countries have gone further in this route than others, but notably Argentina, Chile and Peru are perhaps among those that have gone furthest. The key to meeting these challenges is political stability and determination. This intent of this study is to give the reader an overview of the social profile and political environment of these three countries as part of the larger business study mission undertaken by the Nanyang Business School MBA students.